A Pyridoindole‐Based Multifunctional Bioprobe: pH‐Induced Fluorescence Switching and Specific Targeting of Lipid Droplets. Issue 18 (17th August 2017) - Sk, Bahadur; Thakre, Pilendra Kumar; Tomar, Raghuvir Singh; Patra, Abhijit
Abstract: A versatile fluorescent probe, PITE, based on alkyl‐substituted pyridoindole (PI) and tetraphenylethylene (TE), which exhibits facile pH‐induced fluorescence switching in solution, as nanoparticles, and in the solid state, is presented. Strong fluorescence in the solid state, as well as in solution and the aggregated state, allow sensing of toxic acid vapors. Fluorescence "off–on" switching of PITE through exposure to trifluoroacetic acid and triethylamine vapor is visualized by the naked eye. A unified picture of the switchable fluorescence of PITE is obtained by comprehensive spectroscopic investigations coupled with quantum mechanical calculations. Strong fluorescence, a large Stokes shift, high photostability, and biocompatibility of PITE make it a viable probe for subcellular imaging. Extensive fluorescence microscopic studies by employing organisms including lower and higher eukaryotes reveal specific localization of PITE to lipid droplets (LDs). LDs are dynamic subcellular organelles linked to various physiological processes and human diseases. Hence, the specific detection of LDs in diverse organisms is important to biomedical research and healthcare. Isolation of LDs and subsequent colocalization studies ascertain selective targeting of LDs by the easily affordable, lipophilic bioprobe, PITE. Thus, PITE is a promising multifunctional probe for chemosensing and the selective tracking of LDs. Abstract : Multifunctional bioprobe : A fluorescent bioprobe based on pyridoindole (PI) and tetraphenylethylene (TE), PITE, showing pH‐responsive fluorescence switching in solution, as nanoparticle, and in the solid state can be used to sense toxic organic acid vapor. PITE is highly specific for the imaging of lipid droplets in diverse organisms under various physiological conditions (see figure).